Coral reef atoll assessment in the South China Sea using Planet Dove satellites. Issue 2 (24th March 2017) - Asner, Gregory P.; Martin, Roberta E.; Mascaro, Joseph
Abstract: Coral reefs of the Spratly archipelago in the South China Sea are undergoing rapid transformation through military base and outpost development, destructive fishing practices and other factors. Despite increasing pressure on the ecologically unique reefs throughout this region, limited direct access to them has made it difficult to monitor reef cover. A new constellation of satellite imaging sensors, called Planet Dove, provides 3–5 m resolution monitoring of Earth on a daily time step, potentially offering a way to monitor changes in reef extent on a rapid repeat basis. We tested the accuracy of Planet Dove data for coral reef and seagrass mapping at an intensively studied atoll in the Spratly archipelago, and then applied the resulting approach to the atolls currently undergoing rapid change in the region. Compared to underwater photographic surveys, we found that unsupervised classification of Planet Dove imagery provided a 92% average accuracy in detecting the extent of shallow coral reef, observable portions of deep coral reef and sand. Dove data were deemed not sufficiently useful for separating different types of shallow reef or seagrass beds. Applying the 3‐class mapping approach to 19 atolls throughout the region, we found that two‐thirds of currently occupied atolls have proportionally less shallow reef cover than unoccupied atolls. Frequent satellite‐based updates of atolls and islands in the Spratly archipelago could advance international discussion on conservation in the South China Sea. Abstract : Coral reefs of the Spratly archipelago in the South China Sea are undergoing rapid transformation, but limited access has made it difficult to monitor and report on resulting coral cover changes. A new constellation of space‐borne imaging sensors, called Planet Dove, was used to assess coral reef extent of atolls undergoing rapid change throughout the region. Two‐thirds of currently occupied atolls have proportionally less shallow reef cover than unoccupied atolls, and several occupied atolls showed severe depletions in reef cover compared to unoccupied atolls. Frequent satellite‐based updates of reef atolls in the Spratly archipelago could enhance international discussion on conservation in the South China Sea.